Mapping Drug Resistance Genes in Plasmodium Falciparum by Genomewide Association - Anderson, Tim J.C. (Current Drug Targets - Infectious Disorders, 2004)
When alleles conferring drug resistance spread through a population of malaria parasites, they leave characteristic “scars” in the parasite genome. Flanking neutral polymorphisms “hitchhike” to high frequency with the resistance mutation, generating deep valleys of reduced variation and broad swathes of elevated linkage disequilibrium around the resistance locus. We can systematically search the genome for these scars by genotyping polymorphic marker loci at intervals throughout the genome of P. falciparum, and use them as signposts for locating drug resistance genes. In this review I outline the rational behind this approach to genetic mapping. I describe key features of P. falciparum population biology, such as recombination rate, inbreeding, and selection intensity that influence the size of genomic regions affected by selection and the choice of study population. I discuss suitable genetic markers, study designs, and statistical approaches to data analysis. Finally, to demonstrate the utility of the approach I describe two proof-of-principle studies documenting patterns of genetic variability around known drug resistance genes.
Keywords: linkage disequilibrium